The nonlinear theory of interaction of ion streams with virtual cathode of the high-current relativistic electron beam - Balakirev, V.A.; Onishchenko, I.N.; Onishchenko, N.I. (Вопросы атомной науки и техники, 2004)
Nonlinear LF dynamics of interaction of the longitudinal ion stream with the electron virtual cathode formed by
high-current relativistic electron beam which is injected in the cylindrical drift chamber is investigated. Both the case of
coincided radii of electron and ion beams, and the case when the radius of ion beam exceeds the radius of electron beam
are considered. Досліджена нелінійна НЧ динаміка взаємодії повздовжнього іонного потоку з електронним віртуальним
катодом, утвореним потужнострумовим релятивістським електронним пучком, який інжектується в
циліндричну камеру дрейфу. Розглянуто як випадок співпадаючих радіусів електронного та іонного пучків, так і
випадок, коли радіус іонного пучка перевищує радіус електронного пучка. Исследована нелинейная НЧ динамика взаимодействия продольного ионного потока с электронным
виртуальным катодом, образованным сильноточным релятивистским электронным пучком, который
инжектируется в цилиндрическую камеру дрейфа. Рассмотрен как случай совпадающих радиусов электронного
и ионного пучков, так и случай, когда радиус ионного пучка превышает радиус электронного пучка.